Taxonomy of the cerapachyine ant genera Simopone Forel, Vicinopone gen. n. and Tanipone gen. n. (Hymenoptera: Formicidae) - Bolton, Barry; Fisher, Brian L. (Zootaxa, 2012)
Taxonomic studies of three cerapachyine ant genera are presented: the Old World tropical Simopone Forel, the Afrotropi-cal Vicinopone gen. n. and the Malagasy endemic genus Tanipone gen. n. Vicinopone is a monotypic genus, the sole spe-cies of which (conciliatrix) was formerly included in Simopone. Ten species of Tanipone are recognised (aglandula,aversa, cognata, hirsuta, maculata, pilosa, scelesta, subpilosa, varia, zona), all of which are newly described here. Thenumber of species of Simopone is increased from 15 to 38 by the description of 9 new Afrotropical species (amana, brun-nea, dryas, latiscapa, miniflava, occulta, persculpta, rabula, vepres), 13 new Madagascan species (consimilis, dignita,dux, elegans, fera, inculta, merita, nonnihil, rex, sicaria, silens, trita, victrix), and the resurrection of one name (wilburi)from synonymy. Modern diagnoses of the genera are included, together with newly designed keys to the Afrotropical and Malagasy species.